(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
The Homeric Hymn to Demeter formed the theme of one of the longest standing mysteries in the ancient world, the Eleusinian Mysteries. Demeter sets on a quest to find her daughter Persephone who, abducted by Hades, is violently taken to the underworld. An existential-phenomenological study of the myth reveals its importance as an ancient testimony to a journey of transformation of consciousness. It is at a crucial point that Iambe and her music completely change the narrative; her word and jest dramatically affect gods and humans alike.